A proposed expansion of the Library of Congress schedule DS 651 to DS 689 for Philippine history - Lee, Verna C. (1988)
The Library of Congress Classification scheme was developed basically for the needs of the users and staff of the Library of Congress. Hence, the applicability of the system to other library situations is limited and inadequate. For Philippine libraries in particular, the LCC division DS651-689 for Philippine history and description fails to meet the current classification needs of Philippine history materials.